2021
DOI: 10.3389/fpsyt.2021.735005
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Co-occurring Mental Disorders and Chronic Physical Illnesses on Frequency of Emergency Department Use and Hospitalization for Mental Health Reasons

Abstract: Background: Patients with mental disorders (MD) are at high risk for a wide range of chronic physical illnesses (CPI), often resulting in greater use of acute care services. This study estimated risk of emergency department (ED) use and hospitalization for mental health (MH) reasons among 678 patients with MD and CPI compared to 1,999 patients with MD only.Methods: Patients visiting one of six Quebec (Canada) ED for MH reasons and at onset of a MD in 2014–15 (index year) were included. Negative binomial models… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 78 publications
1
7
0
Order By: Relevance
“…The finding that women have a higher probability of receiving follow-up care than men is easily explained by their higher reported rates of service use. 55 Study findings also confirmed the second part of our hypothesis, namely that patients receiving better prior GP follow-up care would be more likely to receive follow-up care after an incident MD episode. Patients followed by a senior GP in family medicine groups and those receiving a high continuity of GP care were particularly more likely to get follow-up care after an incident MD episode-family medicine groups have regulations that ensure prompt and continuous care, especially for vulnerable populations.…”
Section: Discussionsupporting
confidence: 80%
See 4 more Smart Citations
“…The finding that women have a higher probability of receiving follow-up care than men is easily explained by their higher reported rates of service use. 55 Study findings also confirmed the second part of our hypothesis, namely that patients receiving better prior GP follow-up care would be more likely to receive follow-up care after an incident MD episode. Patients followed by a senior GP in family medicine groups and those receiving a high continuity of GP care were particularly more likely to get follow-up care after an incident MD episode-family medicine groups have regulations that ensure prompt and continuous care, especially for vulnerable populations.…”
Section: Discussionsupporting
confidence: 80%
“…Follow-up care was also higher in the Montreal metropolitan area, which is not surprising considering specialized care and GP walk-in clinics are usually overrepresented in large urban areas 53 and tend to attract more vulnerable patients such as the homeless and individuals with complex health conditions. 52,54 Studies also reveal that hospitalized patients are among the most vulnerable, 55 which supports current trends seeking to improve discharge planning and continuous care, 56 and to provide better follow-up care for these patients. Those with co-occurring MDs-SRDs 57 and chronic physical illnesses 55 are also known for highly using services, and their complex conditions justify improving follow-up care.…”
Section: Discussionmentioning
confidence: 82%
See 3 more Smart Citations